Tracking nature – the possibilities of introducing permaculture strategies into the historical city centre of Zamość. The Courtyards - Kielin, Katarzyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
The author focuses on the problem of water management in the selected areas and the most adequate, appropriate, relative SUDS solutions for the places in question. The spaces were chosen from the area which was regarded as the most problematic in ’The Local Revitalisation Program for Zamość for the period 2017 to 2023’. Justification for the chosen solutions is based on the geological conditions of the terrain, the existing stormwater management system , the extent of paved surfaces and the quality and quantity of plant cover. Proposed solutions were analysed in the spotlight of permaculture principles. The aim of the paper is to raise awareness of the concepts of SUDS and Permaculture as they complement each other and offer pro-ecological approach to water.